Afrontar la escasez de agua : un marco de acción para la agricultura y la qeguridad alimentaria (Water reports ;, 2013)
"In the 20th Century, water use has increased at more than twice the rate of population growth, to the point that in many regions overall demand for water can no longer be satisfied. Agriculture uses 70 percent of global freshwater withdrawals and is probably the sector where water scarcity is most critical. Under the joint pressure of population growth and changes in dietary habits, food consumption is increasing in most regions of the world, and it is expected that by 2050 an additional 60 percent of food will be needed to satisfy global demand. Future policy decisions will increasingly need to reflect the tight linkage between water and food security, and be based on a clear understanding of opportunities and trade-offs in managing water for agricultural production. In order to guide its action in support of its member countries, FAO has recently embarked on a long-term programme on the theme "Coping with water scarcity -- the role of agriculture". Based on an expert consultation, a conceptual framework has been developed to help address the question of food security under conditions of water scarcity. This report presents the conceptual framework, reviews a series of policy and technical options, and establishes a set of principles that should serve as a basis for the development of effective food security policies in response to growing water scarcity."--Back cover